Excision of fascia in melanoma thicker than 2 mm: no evidence for improved clinical outcome. (1st December 2014) - Hunger, R.E.; Seyed Jafari, S.M.; Angermeier, S.; Shafighi, M.
Summary: Background: Lack of evidence‐based data causes significant variation among surgeons concerning the depth of wide excision for primary cutaneous melanomas. Objectives: To evaluate the clinical effect of excision of the deep fascia in melanomas thicker than 2 mm on patient outcome. Methods: We performed a retrospective cohort review (1996–2012) of patients with melanomas thicker than 2 mm. Included patients underwent excision with a 1‐cm margin. Data collected included the patients' sex, age, tumour location, tumour type, Breslow depth and presence of ulceration. Local recurrences, locoregional and distant metastases, and disease‐free and overall survival were compared between the fascia‐excised and the fascia‐preserved groups. Results: Out of 2182 patients with malignant melanomas, 213 melanomas thicker than 2 mm, with a median follow‐up of 1547 days, were included. The mean age of the patients was 62·6 years and the mean Breslow depth was 4·2 mm. Analysis of data for death attributable to melanoma ( P = 0·72), local recurrence ( P = 0·71), and locoregional ( P = 0·87) and distant metastases ( P = 0·34) were not significantly different between the study groups. Furthermore, Kaplan–Meier and Cox regression analysis of both groups showed no evidence of significant difference regarding disease‐free [ P = 0·35; hazard ratio (HR) 1·25; 95% confidence interval (CI) 0·79–1·97] and overall survival ( P = 0·63; HR 1·18; 95% CI 0·61–2·27). Conclusions: We believe that excision of the deep fascia does not improve the outcome of melanomas thicker than 2 mm.